MIRERC 065/2025; Field Market Experiment: Testing Sales Agents vs. Enumerators in Promoting Agricultural Inputs: Evidence from a Simulated Rural Marketplace - Rahab Kariuki; Murtaza Fazlehussein Karimjee; Pauline Wanjeri; Jackline Chemutai; Mutwiri, Antony (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Executive Summary This research proposal supports the broader objectives of evidence-based rural development and innovative agricultural sales strategies in sub-Saharan Africa. Despite increasing efforts to reach smallholder farmers with high-quality agricultural products, a lack of rigorous evidence on effective sales approaches continues to hinder the scale-up and optimization of last-mile distribution models. In particular, questions remain about the added value of deploying trained sales agents versus lower-cost enumerators in driving product uptake. This experimental study aims to generate practical, actionable insights on farmer purchasing behavior in response to different seller types and sales incentives. Conducted within a controlled yet realistic simulated marketplace, the experiment will compare the sales effectiveness of trained agents and enumerators, and assess which offer structures—such as discounts, savings plans, or bundled services—are most effective in promoting product uptake among rural farmers. The research places strong emphasis on real-world applicability, using genuine financial transactions and locally relevant products to simulate market dynamics. Additionally, the study incorporates farmer profiling and discrete behavioral observation to understand both demand-side drivers and the influence of agent interaction quality on purchasing decisions. By rigorously testing these elements, the study will contribute valuable insights for implementing organizations, funders, and agricultural input providers looking to optimize rural sales strategies, improve farmer outreach, and enhance the cost-effectiveness of agent deployment models.